2006
DOI: 10.1631/jzus.2006.b0769
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium tolerance in barley (Hordeum vulgare L.): Physiological mechanisms, genetics and screening methods

Abstract: Aluminium (Al) toxicity is one of the major limiting factors for barley production on acid soils. It inhibits root cell division and elongation, thus reducing water and nutrient uptake, consequently resulting in poor plant growth and yield. Plants tolerate Al either through external resistance mechanisms, by which Al is excluded from plant tissues or internal tolerance mechanisms, conferring the ability of plants to tolerate Al ion in the plant symplasm where Al that has permeated the plasmalemma is sequestere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(94 citation statements)
references
References 140 publications
(173 reference statements)
5
85
0
4
Order By: Relevance
“…Após 96 horas de crescimento, foram medidos os comprimentos da raiz principal e da raiz secundária maior, com paquímetro digital, modelo 727, (Starret, Ohio, USA). A medida do comprimento das duas raízes maiores é considerada a mais apropriada avaliação para estudos genéticos e moleculares e fornecem uma boa separação dos genótipos tolerantes e sensíveis ao alumínio (Wang et al, 2006).…”
Section: Methodsunclassified
“…Após 96 horas de crescimento, foram medidos os comprimentos da raiz principal e da raiz secundária maior, com paquímetro digital, modelo 727, (Starret, Ohio, USA). A medida do comprimento das duas raízes maiores é considerada a mais apropriada avaliação para estudos genéticos e moleculares e fornecem uma boa separação dos genótipos tolerantes e sensíveis ao alumínio (Wang et al, 2006).…”
Section: Methodsunclassified
“…In recent years, there has been a significant progress on our understanding of the shoot-growth responses of plants to aluminum toxicity and drought (Aftab et al 2010;Beebe et al 2009Beebe et al , 2010Blum 2010;Chaves et al 2003;Chen 2006;Manavalan et al 2009;Okiyo et al 2010;Wang et al 2006;Zhang et al 2007). The effect of Al and drought on shoot and root growth and the factors responsible for the inhibition of root and shoot growth owing to Al toxicity and drought stress are depicted in Fig.…”
Section: Shoot-growth Response Of Plants To Aluminium Toxicity and Drmentioning
confidence: 99%
“…Compiled from Yang et al (2012) It has been reported that Al toxicity restricts the yield of many crops particularly in regions with acid subsoils throughout the world (Sumner et al 1986). Aluminium toxicity decreases drought resistance and the use of subsoil nutrients (Wang et al 2006). Deleterious effects of subsoil soil-acidity on crop yield will thus be influenced by the extent to which a plant depends on the subsoil for supply of water and nutrients, especially when the topsoil dries out (Jozefaciuk and Szatanik-Kloc 2001;Stodart et al 2007;Tang et al 2001Tang et al , 2003a.…”
Section: Interaction Of Aluminium-drought Stresses On Crop Yieldmentioning
confidence: 99%
“…Tolerance to acid soils differs greatly among cereal species, and barley is usually considered the most susceptible crop (Garvin and Carver, 2003;Zhu et al, 2003;Wang et al, 2006;) Paunovic and Madic, 2011. This fact could be used as an explanation for the very friendly response of barely to the applied treatment in our study.…”
Section: Resultsmentioning
confidence: 99%